SOCIALIZATION OF COVID-19 MANAGEMENT IN HEALTH POLYTECHNIC OF KERTA CENDEKIA - Dini Prastyo Wijayanti; Riesmiyatiningdyah Riesmiyatiningdyah; Kusuma Wijaya Ridi Putra; Agus Sulistyowati; Meli Diana; Nima Eka Nur Rahmania; Nina Rizka Rohmawati (Community Service Journal of Indonesia, 2022)
The socialization related to the prevention of COVID-19 in the Health Polytechnic of Kerta Cendekia is a form of concern for the academic community of the Health Polytechnic of Kerta Cendekia in dealing with the spread of COVID-19 in the Health Polytechnic of Kerta Cendekia. This activity was carried out on August 20, 2021 at the Health Polytechnic of Kerta Cendekia campus. The implementation was attended by 90% of the Health Polytechnic of Kerta Cendekia academic community. This is because the Health Polytechnic of Kerta Cendekia academic community did not attend this event due to illness and was on guard at the Security Post to maintain security. The process of implementing this socialization activity was carried out for 3 weeks, starting from the coordination process of community service implementers, preparation, up to the evaluation of the implementation of the socialization activities. The activity went smoothly and the Health Polytechnic of Kerta Cendekia academics were very enthusiastic in participating in the implementation of this socialization activity. The entire Health Polytechnic of Kerta Cendekia academic community who participated in this socialization have been able to understand the implementation of the COVID-19 response and will carry out the implementation of the COVID-19 response in the Health Polytechnic of Kerta Cendekia and wherever they are.